452. OUTCOME OF ESOPHAGEAL RESECTION IN PATIENTS WITH ESOPHAGEAL CANCER WITH HISTOPATHOLOGICALLY CONFIRMED DISTANT METASTASIS. (24th September 2022) - Atanasova, Elena
Abstract: Patients suffering from esophageal cancer with metastatic disease are usually considered not eligible for resection. In selected patients, however, surgery including resection of distant metastasis, is performed. This study aimed to study the frequency and outcomes after surgery for metastatic esophageal cancer. A nationwide cohort study on all patients resected for esophageal cancer in Sweden, between 2006 and 2017, with histopathological verified metastatic disease (pM1). Complete follow-up regarding survival was acquired from the Cause of death registry. Overall survival was analyzed and presented with the Kaplan Meier method and multivariable Cox-regression with Hazard Ratios (HR) with 95% Confidence Intervals (CI). Of 1572 patients who underwent esophageal resection 75 had pM1 disease. Of those, 70% (n = 53) had been preoperatively staged as cM0. Conversely, 3% of patients with pM0 disease were staged as clinical cM1 or cMX prior to surgery. Advanced T or N-stage was more common in M1 patients compared to M0 patients. Additionally, neoadjuvant treatment was less common in M1 compared to M0 patients (40%vs52%) while adjuvant therapy was more common in M1 patients (38%vs14%).Five-year overall survival was significantly lower in M1 compared to M0 patients, 15%vs43% respectively (p < 0.001, log-rank test). In numbers, 11 out of 75 patients were alive after five years. There are long-term survivors among patients with confirmed metastatic esophageal cancer that underwent radical resection. Selection of patients with limited metastatic disease and response to neoadjuvant therapy may contribute to this effect.